Lithium composite oxide for lithium secondary battery and method for producing same
By optimizing the inter-face distance within lithium composite oxide secondary particles and employing a water washing and coating process, the challenges of residual lithium in lithium secondary batteries are addressed, resulting in improved capacity, resistance, and lifetime characteristics.
Patent Information
- Application Number
- JP2023152371
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2016-10-10
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2037-03-30
AI Technical Summary
Lithium secondary batteries face issues with high residual lithium levels, leading to poor high-temperature safety, gelation problems, and reduced capacity and lifetime characteristics in positive electrode active materials.
The development of lithium composite oxide secondary particles with a unique structure, where the inter-face distance between primary particles inside and on the surface of secondary particles is optimized, and a method involving water washing and coating with dissimilar elements to improve lithium ion diffusion pathways and surface characteristics.
This approach effectively reduces residual lithium, enhances capacity, resistance, and lifetime characteristics of lithium secondary batteries, while maintaining improved high-temperature storage characteristics.
Smart Images

Figure 0007648702000011 
Figure 0007648702000012 
Figure 0007648702000013
Abstract
Description
[Technical field]
[0001] The present invention relates to a lithium composite oxide and a manufacturing method thereof, and more particularly, to a cathode active material in which lithium ion diffusion pathways are formed in the a-axis and c-axis directions of a conventional crystal structure, in which water washing is performed in the manufacturing process to improve residual lithium. As a result of the water washing, the residual lithium is reduced, but as a deterioration in performance is induced, a coating of a different element is carried out on the surface, and as the interplanar distance of the crystal structure between the primary particles located inside the secondary particles and the primary particles located on the surface of the secondary particles changes, the lithium composite oxide and its manufacturing method show an effect of improving capacity characteristics, resistance characteristics, and life characteristics. [Background technology]
[0002] As technology and demand for mobile devices increases, the demand for secondary batteries as an energy source is growing rapidly. Among such secondary batteries, lithium secondary batteries, which exhibit high energy density and working potential, long cycle life, and low self-discharge rate, have been commercialized and are widely used. The positive electrode active material used in lithium secondary batteries is mainly lithium-containing cobalt oxide (LiCoO2), with other lithium-containing manganese oxides such as LiMnO2 with a layered crystal structure and LiMn2O4 with a spinel crystal structure, as well as lithium-containing nickel oxide LiNiO2, are also being considered for use. Among the positive electrode active materials, LiCoO2 is the most widely used due to its excellent life characteristics and charge / discharge efficiency, but it has a disadvantage that it has a small capacity and is expensive due to the limited resource of cobalt used as a raw material, so that its price competitiveness is limited when used in large quantities as a power source in medium and large batteries such as electric vehicles. Among the positive electrode active materials, lithium manganese oxides such as LiMnO2 and LiMn2O4 have advantages such as low cost, environmental friendliness, and excellent thermal safety due to the abundant manganese resource used as a raw material, but have problems such as small capacity and poor high temperature characteristics and cycle characteristics.
[0003] A method for preparing a lithium composite oxide generally includes the steps of preparing a transition metal precursor, mixing the transition metal precursor with a lithium compound, and then calcining the mixture. In this case, LiOH and / or Li2CO3 are used as the lithium compound. In general, when the Ni content of the positive electrode active material is 65% or less, Li2CO3 is used, and when the Ni content is 65% or more, it is preferable to use LiOH because it is a low-temperature reaction. However, nickel-rich systems with Ni content of 65% or more have a problem of high residual lithium in the form of LiOH and Li2CO3 on the surface of the positive electrode active material because they are low-temperature reactions. Such residual lithium, i.e., unreacted LiOH and Li2CO3, reacts with electrolyte in the battery, inducing gas generation and swelling, which seriously reduces high-temperature safety. In addition, unreacted LiOH has high viscosity during slurry mixing before manufacturing the electrode plate, which can cause gelation.
[0004] In order to remove such unreacted Li, the present inventors have demonstrated the effect of performing a water washing process after the preparation of an active material, which significantly reduces the amount of residual lithium. However, in this case, the water washing process causes surface damage to the positive electrode active material, which reduces the capacity and efficiency characteristics, and also causes other problems such as increased resistance during high-temperature storage. Thus, a method for reducing the residual lithium and improving the capacity, efficiency, and life characteristics is required. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Republic of Korea Patent Publication No. 10-2011-0108566 Summary of the Invention [Problem to be solved by the invention]
[0006] In order to solve the above problems, the present invention aims to provide a lithium composite oxide having a new structure that reduces residual lithium and improves capacity characteristics, resistance characteristics, and life characteristics. [Means for solving the problem]
[0007] In order to solve the above problems, the present invention provides lithium composite oxide secondary particles, which are secondary particles formed by agglomeration of a plurality of primary particles, and in which, when the inter-plane distance within a primary particle located inside the secondary particle is d1 and the inter-plane distance within a primary particle located on the surface of the secondary particle is d2, the d1 and d2 satisfy the following relational expression: <Relationship> d1>d2
[0008] The inventors have previously filed a patent application for a structure in which a lithium ion diffusion path is formed inside a primary particle of a lithium composite oxide, and the technical feature of the present invention is that the interplanar distance forming such a lithium ion diffusion path is different between primary particles located inside a secondary particle and primary particles located on the surface of the secondary particle. That is, the lithium composite oxide secondary particles according to the present invention are characterized in that the interplanar distance within a primary particle located inside the secondary particle is different from the interplanar distance within a primary particle located on the surface of the secondary particle, and the interplanar distance of the primary particle located inside the secondary particle is larger than the interplanar distance of the primary particle located on the surface of the secondary particle.
[0009] In the secondary particles of the lithium composite oxide according to the present invention, the interplanar distances d1 and d2 refer to the average of 10 adjacent interplanar distances centered on the interplanar distance of a portion measured from a crystal structure analysis result such as a TEM analysis of the positive electrode active material. In the lithium composite oxide secondary particles according to the present invention, the interplanar distance d1 within a primary particle located inside the secondary particle is 4.8 nm or more. In the secondary particles of the lithium composite oxide according to the present invention, the interplanar distance d2 within the primary particles located at the surface portion of the secondary particles is 4.75 nm or less. In the lithium composite oxide secondary particles according to the present invention, the lithium composite oxide secondary particles have a hexagonal structure, and are characterized in that a lithium ion diffusion path is formed from the surface of the particle toward the center.
[0010] In the lithium composite oxide secondary particles according to the present invention, the primary particles located on the surface of the secondary particles refer to primary particles located on the portion coated with a different metal, and in the lithium composite oxide secondary particles according to the present invention, the primary particles located inside the secondary particles refer to primary particles located inside the secondary particles excluding the surface. In the lithium composite oxide secondary particles according to the present invention, when defining the primary particles located on the surface of the secondary particles, the thickness of the surface of the secondary particles is 50 nm to 200 nm from the outermost periphery of the secondary particles. In the lithium composite oxide secondary particles according to the present invention, the surface portion of the secondary particles is characterized in that the concentration of Co ions shows a gradient. In the lithium composite oxide secondary particles according to the present invention, the primary particles located at the surface portions of the secondary particles are characterized in that the Co ion concentration within the primary particles is not constant but exhibits a concentration gradient.
[0011] In the lithium composite oxide secondary particles according to the present invention, the primary particles located on the surface of the secondary particles and the primary particles located inside the secondary particles include concentration gradient parts in which the concentration of Co ions shows a gradient at the boundaries of the primary particles. The secondary lithium composite oxide particles according to the present invention are characterized in that the binding energy (P1) of the spin-orbit-spit 2p3 / 2 peak and the binding energy (P2) of the 2p1 / 2 peak in the Co 2p core-level spectrum analysis obtained through XPS measurement are as follows. 779 eV ≦ (P1) ≦ 780 eV 794 eV ≦ (P2) ≦ 795 eV
[0012] The lithium composite oxide secondary particles according to the present invention are characterized in that the ratio of the peak intensity (I531) around 531 eV and the peak intensity (I528) around 528.5 eV in the O 1s core-level spectrum analysis obtained through XPS measurement is as follows. (I531) / (I528)≦2
[0013] The secondary particles of lithium composite oxide according to the present invention are characterized in that the ratio of the peak intensity (I289) around 289 eV and the peak intensity (I284) around 284.5 eV in the C 1s core-level spectrum analysis obtained through XPS measurement is as follows. (I289) / (I284)≦0.9
[0014] In the lithium composite oxide secondary particles according to the present invention, the secondary particles are represented by the following <Chemical Formula 1>. [ka] (In the <Chemical Formula 1>, M1 is Mn or Al, M2 and M3 are metals selected from the group consisting of Al, Ba, B, Co, Ce, Cr, F, Li, Mg, Mn, Mo, P, Sr, Ti, and Zr, and 0.95≦X1≦1.05, 1.50≦a≦2.1, 0.02≦x1≦0.25, 0.01≦y1≦0.20, 0≦z1≦0.20, and 0≦r1≦0.20)
[0015] The present invention also provides A first step of preparing a positive electrode active material precursor for a lithium secondary battery represented by the following <Chemical Formula 2>; [ka] (In the <Chemical Formula 2>, M1 is Mn or Al, and M2 is a metal selected from the group consisting of Al, Ba, B, Co, Ce, Cr, F, Li, Mg, Mn, Mo, P, Sr, Ti, and Zr, (0≦x2≦0.25, 0≦y2≦0.20, 0≦z2≦0.20)
[0016] a second step of reacting the positive electrode active material precursor for a lithium secondary battery with a lithium compound and subjecting the resulting mixture to a first heat treatment to prepare a positive electrode active material; a third step of washing the positive electrode active material with distilled water or an alkaline aqueous solution; a fourth step of mixing and stirring the washed positive electrode active material with a solution containing a metal M2 selected from the group consisting of Al, Ba, B, Co, Ce, Cr, F, Li, Mg, Mn, Mo, P, Sr, Ti, and Zr or a compound containing M2 to coat the surface with M2; a fifth step of drying the positive electrode active material particles; and a sixth step of mixing the dried positive electrode active material with a metal M3 or a compound containing M3 selected from the group consisting of Al, Ba, B, Co, Ce, Cr, F, Li, Mg, Mn, Mo, P, Sr, Ti, and Zr, and performing a second heat treatment to dope the metal M3 into the inside of the particles.
[0017] The present invention also provides a lithium secondary battery comprising the lithium composite oxide secondary particles of the present invention. The lithium secondary battery according to the present invention is characterized in that the residual lithium is 6000 ppm or less. In the method for producing secondary particles of a lithium composite oxide according to the present invention, the first heat treatment is performed at a temperature of 700 to 900°C. In the method for producing secondary particles of a lithium composite oxide according to the present invention, the second heat treatment is performed at a temperature of 400 to 750°C. In the method for producing secondary particles of a lithium composite oxide according to the present invention, the concentration of the solution containing the compound containing M2 is 1 mol % to 10 mol %. Effect of the Invention
[0018] In the lithium composite oxide according to the present invention, the interplanar distance of the crystal structure between the primary particles located inside the secondary particles and the primary particles located on the surface of the secondary particles is changed by coating with a different element and washing with water in the precursor step and / or active material preparation step, so that the secondary battery including the lithium composite oxide according to the present invention shows improved capacity characteristics, resistance characteristics, and life characteristics. [Brief description of the drawings]
[0019] [Figure 1] 1 shows the results of measuring the diffraction pattern and interplanar distance of the LiCoO2 positive electrode active material of Comparative Example 1 of the present invention. [Diagram 2] 4 shows the results of measuring a TEM photograph and an EDX photograph of a positive electrode active material prepared in one embodiment of the present invention. [Diagram 3] 4 shows the results of measuring the diffraction pattern and interplanar distance of a positive electrode active material prepared in one embodiment of the present invention. [Figure 4] 4 shows the results of measuring a TEM photograph and an EDX photograph of a positive electrode active material prepared in one embodiment of the present invention. [Diagram 5] 4 shows the results of measuring the diffraction pattern and interplanar distance of a positive electrode active material prepared in one embodiment of the present invention. [Figure 6] 1 shows the results of measuring the change in concentration of Ni, Co, and Al from the surface portion toward the center portion of a positive electrode active material prepared in an embodiment of the present invention. [Figure 7] 1 shows the results of measuring an EDX photograph of a positive electrode active material prepared in one embodiment of the present invention. [Figure 8] 4 shows the results of measuring the diffraction pattern and interplanar distance of a positive electrode active material prepared in one embodiment of the present invention. [Figure 9] 4 shows the results of measuring a TEM photograph and an EDX photograph of a positive electrode active material prepared in one embodiment of the present invention. [Figure 10] 1 shows the results of measuring the change in concentration of Ni, Co, and Al from the surface portion toward the center portion of a positive electrode active material prepared in an embodiment of the present invention. [Figure 11]1 shows the results of measuring the change in concentration of Ni, Co, and Al toward the center at three points on the surface of a positive active material prepared in an embodiment of the present invention. [Figure 12] 4 shows the results of measuring the diffraction patterns and interplanar distances of the positive electrode active materials prepared in an example of the present invention and a comparative example. [Figure 13] 4 shows the results of measuring the diffraction patterns and interplanar distances of the positive electrode active materials prepared in an example of the present invention and a comparative example. [Figure 14] 4 shows the results of measuring the diffraction patterns and interplanar distances of the positive electrode active materials prepared in an example of the present invention and a comparative example. [Figure 15] 1 shows the results of measuring an EDX photograph of an active material produced in a comparative example of the present invention. [Figure 16] 1 shows the results of measuring an EDX photograph of an active material produced in a comparative example of the present invention. [Figure 17] 4 shows the results of measuring the diffraction patterns and interplanar distances of the positive electrode active materials prepared in an example of the present invention and a comparative example. [Figure 18] 4 shows the results of measuring the diffraction patterns and interplanar distances of the positive electrode active materials prepared in an example of the present invention and a comparative example. [Figure 19] 4 shows the results of measuring the diffraction patterns and interplanar distances of the positive electrode active materials prepared in an example of the present invention and a comparative example. [Figure 20] 1 shows the results of measuring the change in concentration of Ni, Co, and Al from the surface portion toward the center portion of a positive electrode active material prepared in an embodiment of the present invention. [Figure 21] 1 shows the results of measuring the change in concentration of Ni, Co, and Al from the surface portion toward the center portion of a positive electrode active material prepared in an embodiment of the present invention. [Figure 22] 1 shows the results of measuring XRD of positive electrode active materials prepared in an example and a comparative example of the present invention. [Figure 23] 1 shows the results of measuring XRD of positive electrode active materials prepared in an example and a comparative example of the present invention. [Figure 24] 1 shows the results of measuring XRD of positive electrode active materials prepared in an example and a comparative example of the present invention. [Diagram 25] 1 shows the results of measuring XRD of positive electrode active materials prepared in an example and a comparative example of the present invention. [Figure 26] 1 shows the results of XPS measurement of positive electrode active materials prepared in an example and a comparative example of the present invention. [Figure 27a] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 27b] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 27c] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Fig. 27d] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 27e] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 28a] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 28b] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 28c] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Fig. 28d] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 28e] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 29a] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 29b] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 29c]1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 29d] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 29e] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 30a] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 30b] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 30c] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 30d] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 30e] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 31a] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 31b] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Fig. 31c] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Fig. 31d] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. [Figure 31e] 1 shows the results of measuring the characteristics of batteries including the positive electrode active materials prepared in an example and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. <Comparative Example 1> In Comparative Example 1, a commercially available LiCoO2 positive electrode active material was used.
[0021] <Experimental Example> Measurement of distance between crystal structures The diffraction patterns and interplanar distances of the primary particles located on the surface of the secondary particles of the LiCoO2 positive active material of Comparative Example 1 and the primary particles located inside the particles were measured, and the results are shown in FIG. LiCoO2 positive active material particles were placed on a carbon grid, carbon-coated, PT-coated, and sliced with an ion beam in a TEM pretreatment process. The sample was then magnified 20 to 25 million times, and the inter-plane distance of the area to be measured was measured as the average distance of the 10 inter-plane distances on the left and right of the inter-plane distance to be measured. As shown in FIG. 1, the diffraction patterns of the primary particles located inside and on the surface of the secondary particles of the LiCoO2 positive electrode active material all had a hexagonal structure, and the interplanar distances of the primary particles located inside and on the surface of the secondary particles were all measured to be 4.70 nm.
[0022] <Example 1> Preparation of positive electrode active material First, NiCo(OH)2 precursor was prepared by coprecipitation reaction. Li2CO3 and LiOH were added as lithium compounds to the prepared precursor, and Al and Mg were added as M1. The precursor was then subjected to a first heat treatment to prepare a positive electrode active material for lithium secondary batteries. Distilled water was prepared, and the positive active material for a lithium secondary battery was put into the distilled water, and the positive active material for a lithium secondary battery was washed with water while maintaining the temperature. Thereafter, 0.03 mol of cobalt sulfate solution was added to the positive active material washing solution at a constant rate for 1 hour while stirring the positive active material, and the surface of the positive active material was coated with Co in M2, washed with water, and dried at 120° C. under vacuum conditions. The coated positive electrode active material was added with Ti as M3, and subjected to a second heat treatment at 450° C. to produce a positive electrode active material for a lithium secondary battery.
[0023] <Experimental example> TEM, EDX measurement TEM and EDX images of the positive active material prepared in Example 1 were taken, and the results are shown in FIG. As shown in FIG. 2, in the case of the cathode active material prepared in Example 1 of the present invention, the Co concentration is high on the surface of the secondary particles and decreases from the surface to the inside of the secondary particles, indicating that the Co concentration is not constant within the secondary particles but shows a gradient.
[0024] <Experimental Example> Measurement of distance between crystal structures The diffraction patterns and interplanar distances of the primary particles located inside the secondary particles of the cathode active material prepared in Example 1 and the primary particles located on the surface coated with Co and Ti were measured, and the results are shown in FIG. 3. As shown in FIG. 3, the thickness of the Co coating layer is about 80 nm, and the diffraction pattern of the primary particles located inside the secondary particles has a hexagonal structure. In the case of the primary particles located inside the secondary particles, the average interplanar distance of 10 adjacent planes in the TEM photograph was measured to be 4.88 nm, whereas in the case of the primary particles located on the surface where the Co coating layer is present, the diffraction pattern has a hexagonal structure but the interplanar distance was measured to be 4.73 nm. This shows that the interplanar distance of the primary particles located on the surface is reduced compared to the primary particles located inside the secondary particles that are not coated with cobalt, and the interplanar distance of the primary particles located on the surface is changed to be similar to the interplanar distance of LiCoO2 in the comparative example.
[0025] <Example 2> Preparation of positive electrode active material The same procedure as in Example 1 was carried out, and the positive active material of Example 2 was prepared by coating the positive active material with the cobalt aqueous solution added to the positive active material washing solution at a concentration of 4 mol %.
[0026] <Experimental example> TEM, EDX measurement TEM and EDX images of the positive active material prepared in Example 2 were taken, and the results are shown in FIG. As shown in FIG. 4, in the case of the cathode active material prepared in Example 2 of the present invention, the Co concentration is high on the surface of the secondary particles and decreases toward the inside of the secondary particles, so that the Co concentration is not constant but shows a gradient.
[0027] <Experimental Example> Measurement of distance between crystal structures The diffraction patterns and interplanar distances of the primary particles located inside the secondary particles of the positive active material prepared in Example 1 and the primary particles located on the surface portions coated with Co and Ti were measured, and the results are shown in FIG. 5. In FIG. 5, the thickness of the surface Co coating layer is about 90 nm, the diffraction pattern of the primary particles located inside the secondary particles is a hexagonal structure, and in the case of the primary particles located inside the secondary particles, the average interplanar distance of 10 adjacent planes in the TEM photograph is measured to be 4.85 nm, whereas in the case of the primary particles located on the surface where the Co coating layer exists, the diffraction pattern is a hexagonal structure but the interplanar distance is measured to be 4.73 nm. It can be seen that the interplanar distance of the primary particles located on the surface is reduced compared to the primary particles located inside the secondary particles that are not coated with cobalt, and the interplanar distance of the primary particles located on the surface is changed to be similar to the interplanar distance of LiCoO2 in the comparative example.
[0028] <Example 3> Preparation of NCM-based positive electrode active material The same procedure as in Example 1 was carried out, and the positive active material of Example 3 was prepared by coating the positive active material with the cobalt aqueous solution added to the positive active material washing solution at a concentration of 5 mol %.
[0029] <Experimental Example> Concentration scanning The changes in the concentrations of Ni, Co, and Al from the surface of the secondary particles of the positive active material prepared in Example 3 toward the center of the particles were measured, and the results are shown in FIG. In FIG. 6, in the case of the positive active material prepared in Example 3 of the present invention, the Co coating layer in which Co is coated has a higher Co concentration from the surface toward the center, and then the Co concentration decreases toward the center, and the thickness of the Co coating layer is 0.1 um.
[0030] <Experimental example>TEM, EDX EDX images of Ni, Co, and Al were taken from the surface of the secondary particles of the positive active material prepared in Example 3 toward the center of the particles, and the results are shown in FIG. As shown in FIG. 7, in the case of the positive electrode active material prepared in Example 3, the Co concentration increases from the surface toward the center in the Co-coated layer, and then decreases toward the center, with the Co concentration being high along the boundaries of the primary particles.
[0031] <Experimental Example> Measurement of distance between crystal structures The diffraction patterns and interplanar distances of the primary particles located inside the secondary particles of the positive active material prepared in Example 3 and the primary particles located on the surface coated with Co and Ti were measured, and the results are shown in FIG. 8. As shown in FIG. 8, the thickness of the Co coating layer is about 100 nm, the diffraction pattern of the primary particles located inside the secondary particles is a hexagonal structure, and in the case of the primary particles located inside the secondary particles, the average interplanar distance of 10 adjacent planes in the TEM photograph is measured to be 4.84 nm, whereas in the case of the primary particles located on the surface where the Co coating layer is present, the diffraction pattern is a hexagonal structure but the interplanar distance is measured to be 4.67 nm. It can be seen that the interplanar distance of the primary particles located on the Co-coated surface is reduced compared to the primary particles located inside the secondary particles that are not Co-coated, and the interplanar distance of the primary particles located on the surface is changed to be similar to the interplanar distance of LiCoO2 in the comparative example.
[0032] <Example 4> Preparation of NCM-based positive electrode active material The same procedure as in Example 1 was carried out, except that the concentration of the cobalt aqueous solution added to the washing solution for the positive active material was 10 mol %, and washing and coating were performed to prepare a positive active material of Example 4.
[0033] <Experimental example> TEM, EDX measurement TEM and EDX images were taken of the surface of the secondary particles of the positive active material prepared in Example 4, and the results are shown in FIG. As shown in FIG. 9, in the case of the cathode active material prepared in Example 4 of the present invention, the Co concentration is high on the surface of the secondary particles and decreases toward the inside of the secondary particles, so that the Co concentration is not constant but shows a gradient. In addition, the EDX measurement results show that Co is distributed in rod-shaped primary particles, and the Co concentration is measured to be high around the rod-shaped primary particles.
[0034] <Experimental Example> Concentration scanning The changes in the concentrations of Ni, Co, and Al from the surface to the center of the secondary particles of the positive active material prepared in Example 4 were measured, and the results are shown in FIG. As shown in FIG. 10, in the case of the cathode active material prepared in Example 4 of the present invention, the Co concentration increases from the surface toward the center in the coating layer portion where the secondary particles are coated with Co, and then the Co concentration decreases toward the center, and the thickness of the Co coating layer where Co is coated is 0.14 μm.
[0035] <Experimental Example> Concentration scanning The changes in the concentrations of Ni, Co, and Al were measured at three points on the surface of the secondary particles of the positive active material prepared in Example 4 from the surface to the center of the particle, and the results are shown in FIG. As shown in FIG. 11, a concentration gradient layer was uniformly formed in three independent portions of the surface of the secondary particle of the positive active material prepared in Example 4 with a coating layer thickness of 0.14 um.
[0036] <Experimental Example> Measurement of distance between crystal structures The diffraction patterns and interplanar distances of the primary particles located inside the secondary particles of the positive active material prepared in Example 4 and the primary particles located on the surface coated with Co and Ti were measured, and the results are shown in FIG. 12. As shown in FIG. 12, the thickness of the Co coating layer was 140 nm, and the diffraction pattern of the primary particles located inside the secondary particles was a hexagonal structure with an interplanar distance measured at 4.85 nm, whereas the diffraction pattern of the primary particles located on the surface coated with Co and Ti was a hexagonal structure with an interplanar distance measured at 4.69 nm. It can be seen that the interplanar distance of the primary particles located on the Co-coated surface is reduced compared to the primary particles located inside the secondary particles that are not Co-coated, and the interplanar distance of the primary particles located on the surface is changed to be similar to the interplanar distance of LiCoO2 in the comparative example.
[0037] <Experimental Example> Measurement of distance between crystal structures on coating boundary surface FIG. 13 shows the results of measuring the diffraction pattern and interplanar distance at the inside of the primary particle located on the surface of the secondary particle of the positive active material prepared in Example 4 and at the boundary surface of the coating layer within the primary particle located on the surface of the secondary particle. As shown in FIG. 13, the diffraction pattern at the boundary between the primary particles located on the surface of the secondary particles of the positive electrode active material and the coating layer coated with Co and Ti in the primary particles located on the surface of the secondary particles had a hexagonal structure, and the interplanar distance was measured to be 4.71 nm. In the case of the primary particles located inside the secondary particles, the inter-plane distance was measured to be 4.85 nm, and in the case of the primary particles located on the surfaces of the secondary particles coated with cobalt and Ti, the inter-plane distance was measured to be 4.69 nm. In comparison, it can be seen that the inter-plane distance of 4.71 nm at the coating boundary surface within the primary particles located on the surfaces of the secondary particles coated with cobalt and Ti is measured to be the median value between the inter-plane distance of the primary particles located inside the secondary particles and the inter-plane distance of the primary particles located on the surfaces of the secondary particles coated with cobalt and Ti. It can also be seen that the interplanar distance at the coating interface was changed to be similar to that of the LiCoO2 of the comparative example.
[0038] <Experimental Example> Measurement of distance between crystal structures on the boundary surface of primary particles FIG. 14 shows the results of measuring the diffraction pattern and interplanar distance at the boundary between the primary particles and the surfaces of the secondary particles coated with Co and Ti of the positive active material prepared in Example 4. As shown in FIG. 14, the diffraction pattern of the primary particles at the boundary between the primary particles located at the surface of the secondary particle of the positive electrode active material has a hexagonal structure, and the interplanar distances are measured to be 4.69 and 4.71 nm, which are intermediate values between the interplanar distances of the core portion and the coating layer portion. Also, it can be seen that the interplanar distance at the boundary of the primary particles was changed to be similar to the interplanar distance of LiCoO2 of the comparative example.
[0039] <Example 5> Preparation of positive electrode active material The same procedure as in Example 1 was carried out, and the composition of the positive electrode active material for a lithium secondary battery that was subjected to the first heat treatment was Li 1.02 Ni 0.816 Co 0.15 Al 0.034 The positive electrode active material of Example 5 was produced using O2 without adding Ti.
[0040] <Example 6> Preparation of positive electrode active material The same procedure as in Example 1 was carried out, and the composition of the positive electrode active material for a lithium secondary battery that was subjected to the first heat treatment was Li 1.02 Ni 0.903 Co 0.08 Al 0.014 Mg 0.003 O2 to prepare the positive electrode active material of Example 6.
[0041] <Example 7> Preparation of positive electrode active material The same procedure as in Example 1 was carried out, and the composition of the positive electrode active material for a lithium secondary battery that was subjected to the first heat treatment was Li 1.00 Ni 0.965 Co 0.02 Al 0.014 Mg 0.001O2 to prepare the positive electrode active material of Example 7.
[0042] <Example 8> Preparation of positive electrode active material The same procedure as in Example 7 was carried out, except that the concentration of the cobalt aqueous solution added to the washing solution for the positive active material was 4 mol %, to prepare a positive active material of Example 8.
[0043] <Example 9> Preparation of positive electrode active material The same procedure as in Example 7 was carried out, except that the concentration of the cobalt aqueous solution added to the washing solution for the positive active material was 5 mol %, to prepare a positive active material of Example 9.
[0044] <Example 10> Preparation of positive electrode active material The same procedure as in Example 7 was carried out, and the composition of the positive electrode active material for a lithium secondary battery that was subjected to the first heat treatment was Li 1.00 Ni 0.985 Al 0.014 Mg 0.001 O2 to prepare the positive electrode active material of Example 10. The final composition formulas in the above-mentioned Examples 1 to 10 are summarized in the following . [Table 1]
[0045] <Comparative Example 2> The same procedure as in Example 4 was carried out, except that active material particles were added to a 0.1 mol cobalt aqueous solution, stirred, coated, and then dried to prepare a positive active material of Comparative Example 2.
[0046] <Comparative Example 3> A positive active material of Comparative Example 3 was prepared in the same manner as in Example 4, except that Co was not added during washing with water, and the Ti addition process and the second heat treatment were not performed.
[0047] <Experimental example> TEM, EDX measurement TEM and EDX images were taken of the surface of the secondary particles of the positive active material prepared in Comparative Example 2, and the results are shown in FIG. As shown in FIG. 15, in the case of the positive active material prepared in Comparative Example 2, Co is concentrated and distributed on the surface of the particles due to the process of adding active material particles to a cobalt aqueous solution and stirring them, but since a heat treatment process is not performed thereafter, the surface is not flat and Co is not doped into the inside.
[0048] <Comparative Example 4> The same procedure as in Comparative Example 3 was carried out, except that Ti was added at a concentration of 0.001 mol, and a second heat treatment was performed to prepare a positive active material of Comparative Example 4.
[0049] <Comparative Example 5> The positive electrode active material for a lithium secondary battery was prepared in the same manner as in Comparative Example 3, and the first heat treatment was performed. However, the water washing process was not performed after the preparation. Thus, a positive electrode active material of Comparative Example 5 was prepared.
[0050] <Comparative Example 6> The composition of the positive electrode active material for a lithium secondary battery that was subjected to the first heat treatment in the same manner as in Comparative Example 3 was Li 1.00 Ni 0.815 Co 0.15 Al 0.014 O2 to prepare a positive electrode active material of Comparative Example 6.
[0051] <Comparative Example 7> The composition of the positive electrode active material for a lithium secondary battery that was subjected to the first heat treatment in the same manner as in Comparative Example 4 was Li 1.02 Ni 0.903 Co 0.08 Al 0.014 Mg 0.003 O2 to prepare a positive electrode active material of Comparative Example 7.
[0052] <Comparative Example 8> The composition of the positive electrode active material for a lithium secondary battery that was subjected to the first heat treatment in the same manner as in Comparative Example 4 was Li 1.00 Ni 0.965 Co 0.02 Al0.014 Mg 0.001 O2 to prepare a positive electrode active material of Comparative Example 8.
[0053] <Comparative Example 9> The composition of the positive electrode active material for a lithium secondary battery that was subjected to the first heat treatment in the same manner as in Comparative Example 4 was Li 1.00 Ni 0.985 Al 0.014 Mg 0.001 O2 to prepare a positive electrode active material of Comparative Example 9. The final composition formulas in the above-mentioned Comparative Examples 1 to 9 are summarized in the following . The final composition formulas in the first firing in the above-mentioned Comparative Examples 1 to 9 are summarized in the following . [Table 2]
[0054] <Experimental example> TEM, EDX measurement TEM and EDX images were taken of the surface of the secondary particles of the positive active material prepared in Comparative Example 4, and the results are shown in FIG. As can be seen from FIG. 16, in the case of the cathode active material prepared in Comparative Example 4, since the process of coating Co after the preparation of the active material was not performed, the Co concentration was uniformly distributed within the particles, and no Co concentration gradient was observed from the surface to the inside of the particles.
[0055] <Experimental Example> Measurement of distance between crystal structures The diffraction pattern and interplanar distance were measured for the surface portions of the secondary particles of the positive active material prepared in Comparative Example 4, and the results are shown in FIG. As shown in FIG. 17, the diffraction pattern of the surface portion had a hexagonal structure, and the interplanar distance was measured to be 4.85 nm. The diffraction pattern and interplanar distance of the primary particles located inside the secondary particles of the positive active material prepared in Comparative Example 4 were measured, and the results are shown in FIG. As shown in FIG. 18, the diffraction pattern of the primary particles located inside the secondary particles of the positive active material has a hexagonal structure, and the inter-plane distance is measured to be 4.83 nm. It can be seen that when no Co coating is performed, the inter-plane distance between the primary particles located inside the secondary particles of the positive active material and the primary particles located on the surface are almost similar even after the second heat treatment.
[0056] <Experimental Example> Measurement of distance between crystal structures on the boundary surface of primary particles FIG. 19 shows the results of measuring the diffraction pattern and interplanar distance at the boundary surface of the primary particle located on the surface of the secondary particle of the positive active material prepared in Comparative Example 4. As shown in FIG. 19, the diffraction pattern at the boundary of the primary particles located on the surface of the secondary particles was a hexagonal structure, and the interplanar distances were measured to be 4.81 nm and 4.88 nm. In addition, in FIGS. 18 and 19, when no Co coating is performed, the diffraction patterns and interplanar distances inside and on the boundary surfaces of the primary particles are similar.
[0057] <Experimental Example> Concentration scanning The concentrations of Ni, Co, and Al were measured from the surface to the core of the secondary particles of the positive active material prepared in Comparative Example 4, and the results are shown in FIG. It can be seen from FIG. 20 that in the case of the positive active material prepared in Comparative Example 4 of the present invention, the concentrations of Ni, Co, and Al are constant within the particles.
[0058] <Experimental Example> Concentration scanning The concentrations of Ni, Co, and Al were measured in a direction parallel to the surface direction of the primary particles located on the surfaces of the secondary particles of the positive active material prepared in Comparative Example 4. The results are shown in FIG. As can be seen from FIG. 21, in the case of the cathode active material prepared in Comparative Example 4, the concentrations of Ni, Co, and Al are constant within the particles, the Co concentration does not show a gradient because no Co coating is performed, and the interplanar distance is similar between the surface and the interior.
[0059] <Experimental Example> XRD Measurement XRD measurements were performed on the LiCoO2 positive electrode active materials of Example 4 and Comparative Example 1, and the results are shown in FIG. 22 and FIG. As shown in FIGS. 22 and 23, in the case of the Co and Ti coated cathode active material prepared in Example 4 of the present invention, (104), (110), (113), (101), (102), and (003) peaks were detected, similar to the LiCoO2 of Comparative Example 1.
[0060] <Experimental Example> XRD Measurement The positive electrode active material of Comparative Example 2 was subjected to XRD measurement, and the results are shown in FIG. As shown in FIG. 24, in the case of the positive electrode active material produced in Comparative Example 2 of the present invention, only the peak due to Co(OH)2 was detected, and the (104), (110), (113), (101), (102), and (003) peaks that are characteristically detected in LiCoO2 were not detected.
[0061] <Experimental Example> XRD Measurement XRD measurements were performed on the positive active materials of Comparative Example 4, which was not Co-coated, and Example 4, which was Co-coated and then heat-treated. The results are shown in FIG. As shown in FIG. 25, in the case of the positive electrode active material of Comparative Example 4, which does not undergo the Co coating of the present invention, the (104), (110), (113), (101), (102), and (003) peaks that are characteristically detected in LiCoO2 are not detected.
[0062] <Experimental Example> XPS Measurement XPS was measured for the positive electrode active materials of Comparative Example 4, which was not coated with Co, and Example 3, which was coated with a cobalt aqueous solution having a concentration of 5 mol %, and the results are shown in FIG. 26, when cobalt coating is performed during the water washing process according to the present invention, the intensity of the Co 2p peak is greater than that of Comparative Example 4, and most of this peak is due to Co+3. Also, it can be seen that the intensity of the peak due to LI2CO3 is reduced compared to Comparative Example 4.
[0063] <Experimental Example> Residual Lithium Measurement The residual lithium in the composite oxides prepared in Examples 1 to 10 and Comparative Examples 4 to 9 was measured, and the results are shown in Table 3 below. In order to measure the residual lithium, 1 g of the active material was immersed in 5 g of distilled water and stirred for 5 minutes, and the filtrate was dissolved in 0.1 M HCl. The volume of HCl added until the pH of the filtrate reached 5 was measured to analyze the residual lithium of the active material. As can be seen from Table 3 below, in the case of the active material prepared according to the embodiment of the present invention, the amount of residual lithium is significantly reduced compared to the case of Comparative Example 5 where the calcination process is not performed. [Table 3]
[0064] <Manufacturing example> Battery manufacturing The positive electrode active materials prepared in Examples 1 to 10 and Comparative Examples 4, 6 to 9 were mixed with Super-P as a conductive agent and polyvinylidene fluoride (PVdF) as a binder in a weight ratio of 92:5:3 to prepare a slurry. The slurry was uniformly coated on an aluminum foil having a thickness of 15 μm and dried in a vacuum at 135° C. to prepare a positive electrode for a lithium secondary battery. A coin battery was manufactured by a commonly known manufacturing process using the positive electrode and a lithium wheel as counter electrodes, a porous polyethylene film (Celgard LLC, Celgard 2300, thickness: 25 μm) as a separator, and a liquid electrolyte in which LiPF6 was dissolved at a concentration of 1.15 M in a solvent in which ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7.
[0065] <Experimental Example> Battery characteristic measurement - Initial capacity The initial capacities of the batteries manufactured using the active materials manufactured in Examples 1 to 10 and Comparative Examples 4, 6 to 9 were measured, and the results are shown in FIG. 27a (Examples 1 to 4, Comparative Example 4), FIG. 27b (Example 5, Comparative Example 6), FIG. 27c (Example 6, Comparative Example 7), FIG. 27d (Examples 7 to 9, Comparative Example 8), and FIG. 27e (Example 10, Comparative Example 9). 27a to 27e, when Co coating was performed according to the embodiment of the present invention, the capacity and efficiency characteristics were measured to be superior to those of the comparative example. The initial capacity measurement results of the batteries manufactured using the active materials manufactured in Examples 1 to 10 and Comparative Examples 4, 6 to 9 are summarized in Table 4 below. [Table 4]
[0066] <Experimental Example> Battery characteristic measurement Efficiency characteristic The efficiency characteristics of the batteries manufactured using the active materials manufactured in Examples 1 to 10 and Comparative Examples 4, 6 to 9 were measured, and the results are shown in Figure 28a (Examples 1 to 4, Comparative Example 4), Figure 28b (Example 5, Comparative Example 6), Figure 28c (Example 6, Comparative Example 7), Figure 28d (Examples 7 to 9, Comparative Example 8), and Figure 28e (Example 10, Comparative Example 9). 28a to 28e, it was measured that the capacity and efficiency characteristics of the Co-coated battery according to the embodiment of the present invention were superior to those of the comparative example. The efficiency characteristics of the batteries manufactured using the active materials manufactured in Examples 1 to 10 and Comparative Examples 4, 6 to 9 are shown in Table 5 below. [Table 5]
[0067] <Experimental Example> Battery characteristic measurement - Life characteristics The life characteristics of the batteries manufactured using the active materials manufactured in Examples 1 to 10 and Comparative Examples 4, 6 to 9 were measured, and the results are shown in Figure 29a (Examples 1 to 4, Comparative Example 4), Figure 29b (Example 5, Comparative Example 6), Figure 29c (Example 6, Comparative Example 7), Figure 29d (Examples 7 to 9, Comparative Example 8), and Figure 29e (Example 10, Comparative Example 9). 28a to 28e, it can be seen that when Co coating is performed according to the embodiment of the present invention, the life characteristics are improved compared to the comparative example. The results of measuring the life characteristics of the batteries manufactured using the active materials manufactured in Examples 1 to 10 and Comparative Examples 4, 6 to 9 are summarized in Table 6 below. [Table 6]
[0068] <Experimental Example> Battery characteristic measurement - High temperature storage characteristics The high temperature storage characteristics of the batteries manufactured using the active materials manufactured in Examples 1 to 3, 5 to 10 and Comparative Examples 4, 6 to 9 were measured, and the results before storage are shown in Figure 30a (Examples 1 to 3, Comparative Example 4), Figure 30b (Example 5, Comparative Example 6), Figure 30c (Example 6, Comparative Example 7), Figure 30d (Examples 7 to 9, Comparative Example 8), and Figure 30e (Example 10, Comparative Example 9), and the results after storage are shown in Figure 31a (Examples 1 to 3, Comparative Example 4), Figure 31b (Example 5, Comparative Example 6), Figure 31c (Example 6, Comparative Example 7), Figure 31d (Examples 7 to 9, Comparative Example 8), and Figure 31e (Example 10, Comparative Example 9). Referring to Figures 30a to 30e and Figures 31a to 31e, it can be seen that when Co coating is performed according to an embodiment of the present invention, the impedance does not increase significantly after high temperature storage compared to the comparative example, and therefore the high temperature storage characteristics are significantly improved. The results of measuring high temperature storage characteristics of the batteries manufactured using the active materials manufactured in Examples 1 to 3, 5 to 10 and Comparative Examples 4, 6 to 9 are summarized in below. [Table 7]
Claims
1. The lithium composite oxide secondary particles are formed by agglomeration of a plurality of primary particles, When an average of 10 interplanar distances of adjacent crystal structures located inside secondary particles among the plurality of primary particles measured from a diffraction pattern measured by TEM analysis is defined as d1, and an average of 10 interplanar distances of adjacent crystal structures located on the surface portions of the secondary particles measured from a diffraction pattern is defined as d2, the d1 and d2 satisfy the following relational expression, <Relationship> d1>d2 The above crystal structure refers to the crystal structure within the primary particle, The thickness of the surface portion of the secondary particle is 50 nm to 200 nm from the outermost portion of the secondary particle, The secondary particles are represented by the following Chemical Formula 1: 【Chemistry 1】 (In the <Chemical Formula 1>, M1 is Mn or Al, M2 is Co, and M3 is selected from the group consisting of Al, Ba, B, Co, Ce, Cr, F, Li, Mg, Mn, Mo, P, Sr, Ti, and Zr, and 0.95≦X1≦1.05, 1.50≦a≦2.1, 0.02≦x1≦0.25, 0.01≦y1≦0.20, 0<z1≦0.20, 0.786≦1-(x1+y1+z1)<1, and 0≦r1≦0.20)
2. The lithium composite oxide secondary particles according to claim 1 , wherein the lithium composite oxide secondary particles have a hexagonal structure, and a lithium ion diffusion path is formed from the surface of the secondary particles toward the center.
3. The lithium composite oxide secondary particle described in claim 1, characterized in that the surface portion of the secondary particle exhibits a gradient in concentration of Co ions.
4. The lithium composite oxide secondary particle according to claim 1 , wherein a concentration of Co ions shows a gradient at the boundary between the primary particles located inside the secondary particles.
5. The lithium composite oxide secondary particles according to claim 1 , wherein a concentration of Co ions shows a gradient at the boundary between the primary particles located at the surface of the secondary particles.
6. The lithium composite oxide secondary particles according to claim 1, wherein the secondary particles show at least one peak at (104), (110), (113), (101), (102), and (003) positions in an XRD analysis.
7. The secondary particles of the lithium composite oxide according to claim 1, wherein the binding energy (P1) of the spin-orbit-pit 2p3 / 2 peak and the binding energy (P2) of the 2p1 / 2 peak in a Co2pcore-level spectrum analysis obtained through an XPS measurement are as follows: 779eV≦(P1)≦780eV 794eV≦(P2)≦795eV
8. The secondary particles have a peak intensity (I 531 ) and the peak intensity around 528.5 eV (I 528 2. The lithium composite oxide secondary particles according to claim 1, wherein the ratio of (I 531 ) / (I 528 )≦2
9. The secondary particles have a peak intensity (I 289 ) and the peak intensity near 284.5 eV (I 284 2. The lithium composite oxide secondary particles according to claim 1, wherein the ratio of (I 289 ) / (I 284 )≦0.9
10. A first step of producing a positive electrode active material precursor for a lithium secondary battery; a second step of reacting the positive electrode active material precursor for a lithium secondary battery with a lithium compound and carrying out a first heat treatment to produce a positive electrode active material; a third step of washing the positive electrode active material with distilled water or an alkaline aqueous solution; a fourth step of coating the washed positive electrode active material with a solution containing Co; a fifth step of drying the positive electrode active material particles; a sixth step of mixing the dried positive electrode active material with a metal selected from the group consisting of Al, Ba, B, Co, Ce, Cr, F, Li, Mg, Mn, Mo, P, Sr, Ti, and Zr, and performing a second heat treatment to dope the metal into the inside of the particles; 2. The method for producing secondary particles of a lithium composite oxide according to claim 1, comprising:
Citation Information
Patent Citations
Positive electrode active material, nonaqueous electrolyte battery and manufacturing method of positive electrode active material
JP2012018827A
Lithium metal oxide particles coated with a mixture of core material elements and one or more metal oxides.
JP2014523840A
Lithium complex oxide for lithium secondary battery and method of preparing the same
JP2021169405A
Process for the production of lithium-manganese double oxide for lithium ion batteries and lithium-manganese double oxide for lithium ion batteries made by ...
KR1020110108566A
Method for manufacturing cathode active material for lithium secondary battery and cathode active material for lithium secondary battery manufactured thereby
KR1020140081663A